A Collaborative Analysis of Trends in Referrals to the Pennsylvania Student Assistance Program from 2013 to 2018. (20th November 2022) - Sekhar, Deepa L.; Schaefer, Eric W.; Hoke, Alicia M.; Rosen, Perri; Chuzie, Roberta A.; Milakovic, Dana M.
ABSTRACT: BACKGROUND: The Student Assistance Program (SAP) is mandated kindergarten to 12th grade in Pennsylvania schools to address barriers to student academic success. Following student referral, SAP teams use a systematic process to inform recommendations for school or community‐based services. To evaluate program outcomes, a review of student SAP referral trends over a 5‐year period was undertaken. METHODS: The Pennsylvania Network for Student Assistance Services (PNSAS), the state leadership providing oversight of SAP, partnered with Penn State College of Medicine in a retrospective analysis of student referral data from 2013 to 2018. Public school enrollment demographics were used for comparison. Frequencies and percentages were calculated. RESULTS: Referrals (total n = 352, 640) increased by 24% over the 5 years; demographics 55% male, 69% non‐Hispanic white, 16% non‐Hispanic black, and 10% Hispanic. Referrals were most commonly for behavioral concerns (31%). Discontinued referrals (39%) were primarily for parent refusal/no permission. Trends included rising minority and elementary referrals over the study period. CONCLUSIONS: SAP referral demographics were consistent with state public school enrollment race/ethnicity breakdown suggesting lack of systematic bias. The proportion of behavioral referrals was consistent with rising youth behavioral health needs. PNSAS must consider strategies to support rising referral numbers and trends.